2007
DOI: 10.1523/jneurosci.1833-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Brain Oscillations to Attentional Networks

Abstract: Previous studies have suggested the relation of particular frequency bands such as theta (4 -8 Hz), alpha (8 -14 Hz), beta (14 -30 Hz), or gamma (Ͼ30 Hz) to cognitive functions. However, there has been controversy over which bands are specifically related to attention. We used the attention network test to separate three anatomically defined brain networks that carry out the functions of alerting, orienting, and executive control of attention. High-density scalp electrical recording was performed to record syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
262
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(296 citation statements)
references
References 52 publications
32
262
2
Order By: Relevance
“…gamma and beta; Ermentrout et al 2001). This is supported by EEG studies in attentive vs. non-attending conditions (Fan et al 2006), and in vitro acetylcholine modulation produces coherent oscillations in local cortical circuits Fisahn et al 1998). In this report we focused on examining the outcome of cholinergic modulation of the various potassium and leak currents on the spike generating dynamics in model cortical pyramidal neurons by using the PRC as an assay.…”
Section: Discussionmentioning
confidence: 90%
“…gamma and beta; Ermentrout et al 2001). This is supported by EEG studies in attentive vs. non-attending conditions (Fan et al 2006), and in vitro acetylcholine modulation produces coherent oscillations in local cortical circuits Fisahn et al 1998). In this report we focused on examining the outcome of cholinergic modulation of the various potassium and leak currents on the spike generating dynamics in model cortical pyramidal neurons by using the PRC as an assay.…”
Section: Discussionmentioning
confidence: 90%
“…This procedure assumes that the collapsed components of each network are all providing reliable measures of the same process. These assumptions are somewhat perplexing, since numerous ANT studies have reported Flanker X Cue interactions (i.e., Costa, Hernández, Sebastián-Gallés, & 2008;Fan, Byrne, et al, 2007;Johnson et al, 2008;Oberlin, Alford, & Marrocco, 2005;Redick & Engle, 2006). In the present study, we used ANOVAs and correlational procedures to examine the relation between the four executive control measures (no cue executive control, double cue executive control, central cue executive control, and spatial cue executive control), the three measures of alerting (alerting scores for neutral flankers, congruent flankers, and incongruent flankers) and the three measures of orienting (orienting for neutral, congruent, and incongruent flankers).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the higher iGBA amplitude for human faces might reflect the analysis of this information that is not necessary for the categorization of objects. Another process that may be reflected by the increase in iGBA is the allocation of attention, since iGBA has been shown to be modulated by attention Tiitinien et al, 1993, Fan et al 2007, Jensen et al 2007). However, although some have showed that faces "pop-out" in a visual search task when presented among other stimuli (Hershler and Hochstein (2005), others suggested that this effect can be attributed to low-level vision characteristics (VanRullen, in press).…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of these bursts is modulated by physical stimulus attributes such as size, contrast and spatial-frequency spectrum (Gray et al, 1990;Bauer et al, 1995, Busch et al, 2004, perceptual factors acting bottom-up, such as the ability to form coherent gestalts Tallon-Baudry et al, 1996), and top-down acting factors such as attention Tiitinien et al, 1993, Fan et al 2007 or memory (Osipova et al, 2006;Gruber and Müller 2006;Gruber et al, 2004;TallonBaudry et al, 1998, 2001, Jensen et al 2007. In concert, these bottom-up and top-down modulations raised the hypothesis that iGBA reflects the integration of sensory input with preexistent memory representations to form experienced entities (Tallon-Baudry 1997, 2003).…”
mentioning
confidence: 99%